2021
DOI: 10.1001/jamahealthforum.2021.2924
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postoperative Opioid Prescriptions Before and After Implementation of a Mandatory Prescription Drug Monitoring Program

Abstract: IMPORTANCE Legislation mandating consultation with a prescription drug monitoring program (PDMP) was implemented in California on October 2, 2018. This mandate requires PDMP consultation before prescribing a controlled substance and integrates electronic health record (EHR)-based alerts; prescribers are exempt from the mandate if they prescribe no more than a 5-day postoperative opioid supply. Although previous studies have examined the consequences of mandated PDMP consultation, few have specifically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…There was no change in the amount of opioids prescribed from 2010 to 2020. This runs counter to other studies' findings, which has shown there was a decrease over time [10,13,17,23,29,34]. For example, Reid et al [23] examined trends in patients undergoing orthopaedic procedures before and after legislation in Rhode Island instituting strict prescription limits on providers.…”
Section: Discussion Of Key Findingsmentioning
confidence: 83%
See 1 more Smart Citation
“…There was no change in the amount of opioids prescribed from 2010 to 2020. This runs counter to other studies' findings, which has shown there was a decrease over time [10,13,17,23,29,34]. For example, Reid et al [23] examined trends in patients undergoing orthopaedic procedures before and after legislation in Rhode Island instituting strict prescription limits on providers.…”
Section: Discussion Of Key Findingsmentioning
confidence: 83%
“…Recent well-publicized lawsuits have also highlighted the contribution of pharmaceutical companies to this problem [8]. Because of this, efforts are being made nationally to decrease opioid prescribing [17,23,29].…”
Section: Introductionmentioning
confidence: 99%
“…37 With respect to surgery, a large cross-sectional study of more than 93 000 patients undergoing general surgery, obstetric/gynecologic surgery, or orthopaedic surgery demonstrated initiation of a statewide drug monitor program was associated with an immediate decrease in opioid prescribed prescriptions across all 3 subspecialties. 38 With respect to risk factors for persistent opioid use, we found risk to be multifactorial. Comparing the opioid-naïve vs opioid persistence groups, we found risk factors to include the following: obesity, ASA ≥3, diabetes, opioid prescription within 60 days preoperatively, patients with cervical stenosis, patients undergoing multi-level lumbar posterior spinal fusion, and patients undergoing multi-level cervical fusion.…”
Section: Discussionmentioning
confidence: 85%
“…Over the past 3 decades, decision support prompts in electronic health record (EHR) systems have been used to facilitate clinical practice. 9 A recent study found an association between EHR alerts and changes in postoperative opioid prescriptions, 10 but to nudge clinician behavior toward achieving legislative goals, a broader study incorporating a wide range of clinical settings is warranted. At Kaiser Permanente Southern California (KPSC), 16 categories of prompts were implemented to support AB 2760–based clinical decision-making for outpatient opioid prescription.…”
Section: Introductionmentioning
confidence: 99%